PROGRAM OF COURSE OF PAINTING IN THE SYSTEM OF PREPARATION O OF STUDENTS OF THE SPECIALTY “FINE ART” - Tomashevskiy, V.V. (Pedagogy of Higher and Secondary Education, 2022)
The reference program of course of painting is given in the article, in the conditions of introduction of elements of the credit-module departmental teaching, its aims and tasks are outlined, well-organized and given descriptions of the rich in content modules, prospect of further researches in this region